Characterization of atmospheric structures observed by a VHF MST-type radar in the troposphere over Santa Cruz, Costa Rica - Garbanzo Salas, Marcial (2019)
Results from the frst VHF profler research radar in Costa Rica, operating at a central radar frequency of 46.6 MHz, are presented. Emphasis has been on studies of scattering layers detected in the altitude range 1–6 km, with the main goal being to identify regions with radar echoes and observe the temporal evolution of the echoes. Data were obtained over the course of a full year using a vertical resolution of better than 100 m. Layers of strong scatter were observed regularly, often with simultaneous broad spectra, which may indicate enhanced turbulence. Similar layers have been observed over equatorial Indonesia, and these have been associated with the planetary boundary layer. The presence of echo layers was more common during the dry-season months (December–April); in fact during March, two layers were observed in the lower troposphere for more than 35% of the time. Stable pattern structures often occurred for extended periods, but at times the layers could also vary drastically in behavior from 1 day to the next. After sunset, strong echo layers could persist for several hours. Some examples of regularly observed layer behavior are given.